Evaluation of Intermediate School EFL Textbooks from Teachers’ Perspectives: تقييم كتب اللغة الإنجليزية كلغة أجنبية في المدرسة المتوسطة من وجهة نظر المعلمين (Journal of Faculty of Education, 2022)
تلعب الكتب المدرسية دورًا هاما في تعليم وتعلم اللغة.  تهدف الدراسة إلى تقييم سلسلة الكتب المدرسية في منهج اللغة الإنجليزية كلغة أجنبية FullBlast   المستخدمة في المدارس المتوسطة في السعودية من وجهة نظر المعلمات بالمدينة المنورة. استخدمت الدراسة المنهج الوصفي وجمعت البيانات باستخدام الاستبانة للكشف عن تصورات 71 معلمة حول الكتاب المدرسي معتمدة في التقييم على معايير المحتوى العالمية التالية: التخطيط والتصميم، الأهداف، الموضوعات والمفردات ، القواعد، مهارات اللغة ، الأنشطة والتمارين ، المواد التكميلية ، والثقافة. اوضحت نتائج الدراسة إلى رضا المعلمين بشكل عام عن الكتاب المدرسي من حيث جميع المعايير التسعة.  كما أسفرت النتائج أن معيار التصميم حصل على أعلى متوسط ​​حسابي، بينما حصلت الأنشطة والتمارين على أدنى متوسط حسابي. كما كشفت الدراسة نتائج أخرى عن مزايا وعيوب الكتاب المدرسي. أخيرًا اقترحت الدراسة  بعض التوصيات التي تساعد مصممي المناهج لمعالجة العيوب في الكتب المدرسية للغة الإنجليزية كلغة أجنبية.Textbooks play a significant role in language teaching and learning. This study aimed to evaluate the FullBlast EFL textbook series used in Saudi intermediate schools from the perspectives of female teachers in Al Madinah. The study used the descriptive method. Data was collected by a questionnaire that explored 71 teachers’ perceptions of the textbook depending on the following global content standards: layout and design, objectives, topics, vocabulary, grammar, language skills, activities and exercises, supplemental materials, and culture. The findings of the study showed that teachers were generally satisfied with the textbook in terms of all nine standards. The layout and design standards received the highest mean score, whereas activities and exercises received the lowest. Further results revealed the textbook’s advantages and disadvantages. Finally, the study suggests some recommendations for curriculum designers intended to address the disadvantages that influence EFL textbook delivery.
Keywords: EFL teachers; EFL textbook; Evaluation; Textbook Series